2014
DOI: 10.5604/12321966.1129928
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postnatal exposure of children to tobacco smoke during the first four years of life – observations of the authors

Abstract: The study comprised 318 children in their first four years of life, treated for various medical conditions. The examined children were divided into two groups, Group 1--children exposed to Tobacco smoke--and Group 2--a control group with children from non-smoking families. History data were obtained on the basis of a specially designed questionnaire, used by the doctor in an individual conversation with parent. In each third child from the group 1 cotinine concentration in urine was assayed by the method of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Urinary cotinine levels were found to be statistically higher in children whose parents were smokers, female gender, whose father had a low educational level, and who had 3 or fewer rooms in their house. Similar to our study, Kamer et al reported that the younger age of parents, lower education level, and poor living conditions increase exposure to smoking at home 25 . In another study, likewise, ETS exposure was higher among adolescents in Kuwait, especially those with families with poor socioeconomic status and low parental education levels 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Urinary cotinine levels were found to be statistically higher in children whose parents were smokers, female gender, whose father had a low educational level, and who had 3 or fewer rooms in their house. Similar to our study, Kamer et al reported that the younger age of parents, lower education level, and poor living conditions increase exposure to smoking at home 25 . In another study, likewise, ETS exposure was higher among adolescents in Kuwait, especially those with families with poor socioeconomic status and low parental education levels 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Cotinine concentration in the saliva is related to the number of cigarettes smoked. Cotinine concentration in both in non-stimulated and stimulated saliva obtains similar values [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 59%